2021
DOI: 10.3390/math9060645
|View full text |Cite
|
Sign up to set email alerts
|

Predicting PM2.5 and PM10 Levels during Critical Episodes Management in Santiago, Chile, with a Bivariate Birnbaum-Saunders Log-Linear Model

Abstract: Improving air quality is an important environmental challenge of our time. Chile currently has one of the most stable and emerging economies in Latin America, where human impact on natural resources and air quality does not go unperceived. Santiago, the capital of Chile, is one of the cities in which particulate matter (PM) levels exceed national and international limits. Its location and climate cause critical conditions for human health when interaction with anthropogenic emissions is present. In this paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…5 and PM 10 at the same time. The results showed that the two pollutants have a strong relationship [17]. Due to the city being the spatial carrier of the above sources, one changes in response to the changes of others.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…5 and PM 10 at the same time. The results showed that the two pollutants have a strong relationship [17]. Due to the city being the spatial carrier of the above sources, one changes in response to the changes of others.…”
Section: Introductionmentioning
confidence: 94%
“…Puentes et al took Santiago, the capital of Chile, as an example, and used a bivariate regression prediction model to estimate the PM levels related to PM 2.5 and PM 10 at the same time. The results showed that the two pollutants have a strong relationship [ 17 ]. Due to the city being the spatial carrier of the above sources, one changes in response to the changes of others.…”
Section: Introductionmentioning
confidence: 99%
“…Models were created for daily averaged data from two stations using weather data and addictional seasonal informations. A similar approach was presented by the authors of [ 4 ]. The authors used a bivariate predictive model based on GBS distribution to predict next-day maximum PM 10 and PM 2.5 levels.…”
Section: Introductionmentioning
confidence: 94%
“…In summer, emissions from the municipal and household sectors decrease; therefore, emissions only come from households that use solid-fuel furnaces to heat water. As in other highly polluted cities, such as Santiago, Chile, it should be noted that topographic (poor ventilation), meteorological (low temperature at winter), and socio-economic (coal-fired home heating) conditions negatively affect air quality in the city, especially during the winter period [ 4 ]. Another source of emissions that is visible especially in large cities and agglomerations is transport, which accounts for around 5% of PM 10 emissions, 4% of PM 2.5 emissions, and 44% of NO x emissions for the whole voivodeship [ 30 ].…”
Section: Air Quality Assessment For the City Of Krakowmentioning
confidence: 99%
See 1 more Smart Citation